First molecular detection of porcine circovirus type 2 in bovids in China - Shao-Lun Zhai; Rui-Ai Chen; Sheng-Nan Chen; Xiao-Hui Wen; Dian-Hong Lv; Da-Cheng Wu; Jie Yuan; Zhong Huang; Xiu-Rong Zhou; Man-Lin Luo; Dong-Sheng He; Wen-Kang Wei (Virus Genes, 2014)

Interferon-γ produced by tumor-infiltrating NK cells and CD4+ T cells downregulates TNFSF15 expression in vascular endothelial cells - Yi Lu; Xin Gu; Li Chen; Zhi Yao; Juan Song; Xiulong Niu; Rong Xiang; Tao Cheng; Zhihai Qin; Weimin Deng; Lu-Yuan Li (Angiogenesis, 2014)

Effects of urbanization variables on model parameters for watershed divisions - Rong-song Chen; Wen-Nan Chuang; Shin-jen Cheng (Hydrological Sciences Journal, 2014)

Changes in the potential habitats of 10 dominant evergreen broad-leaved tree species in the Taiwan-Japan archipelago - Katsuhiro Nakao; Motoki Higa; Ikutaro Tsuyama; Cheng-Tao Lin; Shih-To Sun; Jian-Rong Lin; Chyi-Rong Chiou; Tzu-Ying Chen; Tetsuya Matsui; Nobuyuki Tanaka (Plant Ecology, 2014)

Comparative genomics of the marine bacterial genus G laciecola reveals the high degree of genomic diversity and genomic characteristic for cold adaptation - Qi‐Long Qin; Bin‐Bin Xie; Yong Yu; Yan‐Li Shu; Jin‐Cheng Rong; Yan‐Jiao Zhang; Dian‐Li Zhao; Xiu‐Lan Chen; Xi‐Ying Zhang; Bo Chen; Bai‐Cheng Zhou; Yu‐Zhong Zhang (Environmental Microbiology, 2014)
Summary To what extent the genomes of different species belonging to one genus can be diverse and the relationship between genomic differentiation and environmental factor remain unclear for oceanic bacteria. With many new bacterial genera and species being isolated from marine environments, this question warrants attention. In this study, we sequenced all the type strains of the published species of G laciecola , a recently defined cold‐adapted genus with species from diverse marine locations, to study the genomic diversity and cold‐adaptation strategy in this genus. The genome size diverged widely from 3.08 to 5.96 M b, which can be explained by massive gene gain and loss events. Horizontal gene transfer and new gene emergence contributed substantially to the genome size expansion. The genus G laciecola had an open pan‐genome. Comparative genomic research indicated that species of the genus G laciecola had high diversity in genome size, gene content and genetic relatedness. This may be prevalent in marine bacterial genera considering the dynamic and complex environments of the ocean. Species of G laciecola had some common genomic features related to cold adaptation, which enable them to thrive and play a role in biogeochemical cycle in the cold marine environments.

The Report of Sustained Low-Efficiency Dialysis (SLED) Treatment in Fifteen Patients of Severe Snakebite - Junzhang Cheng; Dan Wang; Shouliang Hu; Hong Jiang; Hongzhu Lu; Qingfeng Lei; Juncheng Liu; Fanli Yuan; Rong Chen (Cell Biochemistry and Biophysics, 2014)

Electrosprayed Microparticles with Loaded pDNA-Calcium Phosphate Nanoparticles to Promote the Regeneration of Mature Blood Vessels - Xueqin Guo; Tian Xia; Huan Wang; Fang Chen; Rong Cheng; Xiaoming Luo; Xiaohong Li (Pharmaceutical Research, 2014)

Neuroglobin Promotes Neurite Outgrowth via Differential Binding to PTEN and Akt - Li Li; Qian Rong Liu; Xin Xin Xiong; Ju Mei Liu; Xiao Jing Lai; Chun Cheng; Feng Pan; Yong Chen; Shang Bin Yu; Albert Cheung Hoi Yu; Xiao Qian Chen (Molecular Neurobiology, 2014)

Charlson comorbidity index helps predict the risk of mortality for patients with type 2 diabetic nephropathy - You-Qun Huang; Rong Gou; Yong-Shu Diao; Qing-Hua Yin; Wen-Xing Fan; Ya-Ping Liang; Yi Chen; Min Wu; Li Zang; Ling Li; Jing Zang; Lu Cheng; et al. (Journal of Zhejiang University-SCIENCE B, 2014)